Entre usuários e traficantes: múltiplos discursos “sobre” e “da” atuação dos agentes de segurança na região da “cracolândia” - Souza, Letícia Canonico de (2015)
The present research is guided in discourse analysis "about" and "the" practice of security officers at "Cracolândia" (or Crackland) - located in the central region of São Paulo. The main purpose is to identify the differentiation between users and drug dealers by the officers. The empirical view focuses the Municipal Program to Combat Crack and Other Drugs, entitled "Open Arms", which foresees the intersectorality between the work of Social Welfare, Health and Public Safety in the "fight" to crack. I discuss my object from the speeches of security officers, social workers, health workers and crack users on how policing will be in the region as well as on how it is performed in practice. Documental and field research was performed with different agents that act on the management and use of crack users in the region of "Cracolândia". From the field data, it was possible to note the production of a criminal selectivity in how to operationalize the distinction between users and dealers, question to which I would like to give attention. Thus, I try to fill a gap in the studies of public policies to combat the drug in relation to the apparatus of control exercised by state agents of public security in the region of "Cracolândia".